First report of Neospora caninum infection in pigs in China. Issue 1 (28th September 2019) - Gui, Bin‐Ze; Lv, Qiu‐Yan; Ge, Meng; Li, Run‐Cheng; Zhu, Xing‐Quan; Liu, Guo‐Hua
Abstract: Neospora caninum is a protozoan parasite which can infect many mammals and birds with a worldwide distribution. However, no molecular data are available about the occurrence of N. caninum in pigs. In this study, the serological and molecular prevalence of N. caninum infection in farmed pigs were investigated in Hunan province, China, between January 2017 and December 2018. A total of 1, 500 serum samples collected from 10 herds in Hunan province were evaluated using a competitive‐inhibition enzyme‐linked immunoassay assay (cELISA). The overall seroprevalence of N. caninum in the examined pigs was 1.9%. The seroprevalence of N. caninum ranged from 0.3% to 4.6% among different regions in Hunan province of China ( p  < .05). DNA was extracted from brain samples, and the Nc‐5 gene and ITS‐1 region were amplified and then sequenced. Three (0.5%) of the examined 600 brain tissues were found to contain N. caninum DNA. Our phylogenetic analyses indicated that N. caninum samples were classified into two distinct groups. Although the prevalence is low within the pig groups investigated, our results revealed the emergence of N. caninum infection in pigs in China. The finding of the present study provides molecular evidence that the pigs are the natural intermediate host of N. caninum and may have major epidemiological importance.